ONLINE SHOPPING MOTIVES OF MICRO, SMALL AND MEDIUM ENTERPRISES' PRODUCTS TOWARDS NEW NORMAL ERA - Pasaribu, Popy Novita; Megawati, Dewi; Wibowo, Agung; Suharti, Titing; Muniroh, Leny (Universitas Brawijaya, Indonesia, 2023)
The study aimed to see the nexuses of motives on behavior intention online shopping of MSMEs products in Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas with Price, Halal, and Food Product as moderator variables. The research was conducted using quantitative methods. The data analysis used in this research were validity and reliability tests for instrument tests. The assumption classical tests were the heteroscedasticity, multicollinearity, and multiple linear regression tests. Multiple linear regression tests were t-test, F test, and Moderated Regression Analysis (MRA), calculated using the SPSS 26 application. Results are Hedonic motivation, perceived usefulness, and external subjective norms gave a positive and significant effect on behavior intention online shopping. Price as the moderator variable on Hedonic motivation and perceived usefulness did not have a significant influence, similarly for the result of Halal as the moderator variable on the internal subjective norm and external subjective norm. The interaction with Price and Halal as moderators has a positive effect. Oppositely, Food Products as a moderator variable of the pandemic covid-19 possess a negative response. The contribution of the research can be used by e-commerce, specific sellers, and others where the level of halalness is still very much considered by consumers. The implication for the price is not an issue for online shopping of MSME products in moderating motives, while food product negatively moderates the pandemic covid 19 towards online shopping. Therefore, online food sellers should consider applying the health protocol if there is a new wave of pandemic toward a new normal era to anticipate a negative response.